PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK MENINGKATKAN PEMAHAMAN NILAI-NILAI KEISLAMAN DI KELAS XI DKV SMK MUHAMMADIYAH 2 GRESIK. - Muyasaroh Muyasaroh; Nurul Sholilkhah; Mohammad Amiril Fauzi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
Starting from the importance of technology-based learning and characteristic extend sharp of millennials who love to utilize Android-based Handphones, then researchers have been researching developing learning media, especially in improving Islamic values that are in the field of worship that is a care of the body. aims to (1) establish Android-based learning media on body care materials. (2) To test the feasibility of learning media developed (3), know the level of students ' understanding of the care of the body using Android media. This type of research is development. Adopting the model of Addie's development model, according to Sugiono, consists of five phases that include analysis (analysis), design (design), development, implementation, and evaluation (assessment). The results of the research show the effect of media-based learning Android using Unity application and games, i.e., "learn" application; development of Android-based media judged by experts and media users seen from the material perspective and media the value of percentage 94.69%. At the same time, the latter can increase students' understanding of the body care material through the use of Android media based on the average class value in the first cycle of 73.07. While on the second cycle is average 81.53 so that students' understanding is declared increased.